2019
DOI: 10.4084/mjhid.2019.036
|View full text |Cite
|
Sign up to set email alerts
|

ECONOMIC EVALUATION OF CHELATION REGIMENS FOR Β--Thalassemia MAJOR: A SYSTEMATIC REVIEW

Abstract: Background:Deferoxamine (DFO) or Deferiprone (DFP) or Deferasirox (DFX) monotherapy and DFO and DFP combination therapy were four commonly implemented now chelation regimens for the iron overloaded of β-thalassemia major. This systematic review aims to determine the cost-effectiveness of four chelation regimens and provide evidence for the rational use of chelation regimens for β-thalassemia major therapy in clinic.Methods:A systematic literature search in PubMed, EMBASE (Ovid), CENTRAL (Cochrane library), HTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…A systematic literature review of the costeffectiveness of the four chelation regimens for β-TM 19 showed that DFP was the dominant strategy, which was consistent with the findings of this study. In the systematic literature review, DFX and DFO were tied as the second most cost-effective treatment regimen, and we could not judge which one was more costeffective.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…A systematic literature review of the costeffectiveness of the four chelation regimens for β-TM 19 showed that DFP was the dominant strategy, which was consistent with the findings of this study. In the systematic literature review, DFX and DFO were tied as the second most cost-effective treatment regimen, and we could not judge which one was more costeffective.…”
Section: Resultssupporting
confidence: 90%
“…In addition to the cardiac complication, the major complications of iron overload include chronic liver disease, diabetes mellitus, hypogonadism, hypoparathyroidism, and hypothyroidism. 19,23,24 The Both Chinese and English search terms were used. The search terms included "thalassemia," "betathalassemia," "iron overload," "iron-chelating agents," "deferoxamine," "deferiprone," and "deferasirox," and their variations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The one-step synthetic method is currently utilised by all manufacturers of L1 worldwide and make L1 less expensive than DF and DFRA. [23][24][25][26][27] Deferiprone became a generic drug about 15 years ago, and by comparison, its sale price in India, Iran and Thailand is about 5-10 times cheaper than that sold in western countries. [23][24][25][26][27] A fierce competition against L1 and related controversies were in process from the time of the L1 discovery until today.…”
mentioning
confidence: 99%